NOVQA AS A TOURISM VILLAGE - Sanaeva Lola Shukurboevna; Shaymatov Sayfulla Raxatullaevich (Web of Journals Publishing, 2025)
Many villages in the Jizzakh region are located on the territory of ecotourism zones and nature reserves. The village of Peshagar, Zominsky district, is one of such villages. This village is a place with high potential for ecotourism with its valleys, natural caves, mountain forest landscapes and clean air.
Keywords: Ecotourism, pilgrimage, ethnotourism, natural cave, streams, mountain landscapes, ethnographic museum, customs, traditions, rituals.